PATOGENISITAS CENDAWAN Lecanicillium sp. PTN01 TERHADAP PENGGEREK TONGKOL JAGUNG Helicoverpa armigera (HUBNER) (LEPIDOPTERA: NOCTUIDAE) - Sempurna Ginting; Teguh Santoso; Yayi Munara; Ruly Anwar; Lisdar Sudirman (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Helicoverpa armigera is one of the most important agricultural pests because it has a high reproductive rate and resulted in economic losses. One of the H. armigera control techniques that is in accord with IPM principle is the utilizing of entomopathogenic fungus. The aim of this research was to test the pathogenicity of Lecanicillium (Lecanicillium sp. PTN01) against H. armigera. Pathogenicity test was conducted by conidia application of Lecanicillium sp. PTN01 on both the larvae and eggs at density of 105, 106, 107 conidia/ml. The control group was only treated with steril water. Polymerase chain reaction (PCR) was performed for molecular identification Lecanicillium sp. PTN01. The results showed that Lecanicillium sp. PTN01 able to inhibit egg hatching 13.75%, and cause mortality of first instar larval survival 98.75%. The result of virulence test to the highest larval mortality at 107 conidia/ml density was 41,25%, with the values of LT25, 50, 75 were 3.95, 7.12, 12.82 (days) and LC25, 50, 75 were 4.6 x 105, 1.7 x 106, 4.6 x 109 (conidia/ml). The DNA sequence analysis of ITS 1 and ITS 4 primers showed that Lecanicillium sp. PTN01 was similar to fungus species L. kalimantanense strain BTCC F23 with 94% homology.